THE CONCEPT OF "ADVERTISING" AND ITS IMPORTANCE IN RAISING SOCIAL AWARENESS - Khalikulova , Musharraf; Yevgeniya, Yugay (Innovative Development in Educational Activities, 2023)
This article is devoted to the description of the social advertising and its importance in communication as material for language learning. Moreover, the meaning of the concept of “advertising”, the text of the advertisement and its classification are discussed.